Ethnomathematics Challenges and Opportunities in Mathematics Research and Learning: A Bibliometric Study Using the VosViewer - Trimurtini Trimurtini; SB Waluya; Zaenuri Zaenuri; Nur Karomah Dwidayati; Iqbal Kharisudin (Universitas Negeri Semarang, 2021)
The ethnomathematics approach could complement mathematics learning at all levels of education. This study aims to determine the progress map of the ethnomathematics research. The literature review was carried out from April to May 2021 by searching through the Scopus, Google Scholar, and Crossref database using ‘ethnomathematics’ as the keyword with the help of the VosViewer software. The results showed the development of research and publications on ethnomathematics in the last twelve years (2015 to 2021) from three international databases including Scopus with 200 articles, Crossref with 142 articles, and Google Scholar with 840 articles. The progress map of the ethnomathematics publication based on co-words was grouped into 5 clusters. The authors found four keywords; pedagogy, problem-solving ability, elementary school student, and teaching materials in the collected ethnomathematics publications that can be developed for future research and learning studies at Elementary School Teacher Education Study Program.